1999
DOI: 10.1128/jb.181.22.6987-6995.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory System and Diazotrophic Activity of Acetobacter diazotrophicus PAL5

Abstract: The characteristics of the respiratory system of Acetobacter diazotrophicus PAL5 were investigated. Increasing aeration (from 0.5 to 4.0 liters of air min−1 liter of medium−1) had a strong positive effect on growth and on the diazotrophic activity of cultures. Cells obtained from well-aerated and diazotrophically active cultures possessed a highly active, membrane-bound electron transport system with dehydrogenases for NADH, glucose, and acetaldehyde as the main electron donors. Ethanol, succinate, and glucona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 41 publications
6
25
0
1
Order By: Relevance
“…Features in the 425-431 nm region could have contributions of CO adducts of type-c, type-b and type-a cytochromes (Wood 1984;Kelly et al 1993). The presence of a type-a cytochrome -CO adduct was suggested by a small inflexion at 431 nm, the deep trough at 443 nm and the a-peak at 593 nm; these signals closely resemble those reported for the cytochrome a-CO adduct of cytochrome ba 3 of Gluconacetobacter diazotrophicus (Flores-Encarnación et al 1999). In addition, the presence of a type-d cytochrome-CO adduct was indicated by the a-peak at 640 nm and trough at 626 nm (Jünemann 1997).…”
Section: Cytochrome Content Of the Respiratory Chain Of Gluconacetobasupporting
confidence: 74%
See 1 more Smart Citation
“…Features in the 425-431 nm region could have contributions of CO adducts of type-c, type-b and type-a cytochromes (Wood 1984;Kelly et al 1993). The presence of a type-a cytochrome -CO adduct was suggested by a small inflexion at 431 nm, the deep trough at 443 nm and the a-peak at 593 nm; these signals closely resemble those reported for the cytochrome a-CO adduct of cytochrome ba 3 of Gluconacetobacter diazotrophicus (Flores-Encarnación et al 1999). In addition, the presence of a type-d cytochrome-CO adduct was indicated by the a-peak at 640 nm and trough at 626 nm (Jünemann 1997).…”
Section: Cytochrome Content Of the Respiratory Chain Of Gluconacetobasupporting
confidence: 74%
“…References were oxidized with a small quantity of ammonium persulfate. To obtain the CO-difference spectrum, both cuvette compartments were reduced with glucose, and then, the sample cuvette was bubbled for 5 min with a gently stream of CO, before freezing (Flores-Encarnación et al 1999). To obtain the photodissociation difference spectrum of heme-CO compounds, samples reduced with glucose and bubbled with CO were scanned at 77 K to obtain the prephotolysis spectrum; then, the frozen sample was photolysed with three close shoots of a Vivitar V2000 electronic flash and the postphotolysis spectrum was recorded.…”
Section: Respiratory Activities and Spectral Analysesmentioning
confidence: 99%
“…We previously demonstrated that in N 2 ‐fixing cultures of Ga. diazotrophicus with forced aeration and physiological acidification, the dehydrogenase activities for glucose, ethanol, acetaldehyde, and NADH were maximally expressed (Flores‐Encarnación et al ., ). Accordingly, we show that under the same growth conditions, ADH is largely expressed in its active form (ADHa).…”
Section: Resultsmentioning
confidence: 97%
“…The different activities shown by the enzymes responsible for the direct oxidation of glucose and gluconate, under salt stress, prove that the enzymes, glucose dehydrogenase and gluconate dehydrogenase are sensitive and salt tolerant, respectively. It was expected that both enzymes activities increase under nitrogen fixation, supported by its role in the respiratory protection mechanism of nitrogenase Flores-Encarnación et al 1999). In PAL-3 strain, higher O 2 tolerance of nitrogenase in the presence of glucose and gluconate (substrates of glucose dehydrogenase and gluconate dehydrogenase) was observed by Stephan et al (1991).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors detected a complete tricarboxylic acid cycle in this bacterium, and also respiratory chain-linked enzymes for the oxidation of glucose and keto-gluconates. Glucose dehydrogenase and cytocrome ba are the key components of the respiratory system of G. diazotrophicus during aerobic diazotrophy (Flores-Encarnación et al 1999). Although it does not transport or metabolize sucrose per se , it grows on sucrose because of the extracellular saccharolytic enzyme activity that provides the bacteria with glucose or fructose for growth.…”
Section: Introductionmentioning
confidence: 99%